A case study of technological innovation practice by using Algorithm of Inventive Problem Solving (ARIZ) in IT sector. (May 2017) - Kim, Song-Kyoo
Graphical abstract: Highlights: Systematic innovation applications for high-tech industry sector. Full ARIZ deployment case study. Real world application for systematic innovation usages. Enhanced CPM client is implemented to avoid the complexity of the network system. The research demonstrates the innovation by ARIZ in the IT industry sector. Abstract: This paper deals with the practical approach of the software development in mobile communication industry by using the systematic innovation tools. Converged IP (Internet Protocol) Messaging (CPM) has been the new reusable building blocks to create the variety of interpersonal, interactive and multimedia communication services that run on top of an IP Multimedia Service networks. Even though, full IMS has been discussed more than 10 years, it is hard be deployed because of huge amount of the financial investments. It is also same burden for CPM service because the current CPM service requires additional full IMS infrastructure. ARIZ (Algorithm of Inventive Problem Solving) is applied for developing the new mobile enablers. ARIZ is one of powerful tools in Theory of Inventive Problem Solving that has been designed by a Russian scientist. The paper provides the full deployment of ARIZ-85C for applications in mobile industry. Enhanced CPM client is the alternative client that is implemented to avoid complexities of network systems. This case research also demonstrates a technological innovation by applying ARIZ in the IT industry sector.